Ultra-large chemical libraries for the discovery of high-affinity peptide binders - Quartararo, Anthony J.; Gates, Zachary P.; Somsen, Bente A.; Hartrampf, Nina; Ye, Xiyun; Shimada, Arisa; Kajihara, Yasuhiro; Ottmann, Christian; Pentelute, Bradley L. (Nature communications, 2020)
High-diversity genetically-encoded combinatorial libraries (10 8 −10 13 members) are a rich source of peptide-based binding molecules, identified by affinity selection. Synthetic libraries can access broader chemical space, but typically examine only ~ 10 6 compounds by screening. Here we show that in-solution affinity selection can be interfaced with nano-liquid chromatography-tandem mass spectrometry peptide sequencing to identify binders from fully randomized synthetic libraries of 10 8 members—a 100-fold gain in diversity over standard practice. To validate this approach, we show that binders to a monoclonal antibody are identified in proportion to library diversity, as diversity is increased from 10 6 –10 8 . These results are then applied to the discovery of p53-like binders to MDM2, and to a family of 3–19 nM-affinity, α/β-peptide-based binders to 14-3-3. An X-ray structure of one of these binders in complex with 14-3-3σ is determined, illustrating the role of β-amino acids in facilitating a key binding contact. Synthetic peptide libraries can access broad chemical space, but generally examine only ~ 10 6 compounds. Here, the authors show that in-solution affinity selection, interfaced with nLC-MS/MS sequencing, can identify binders from fully randomized synthetic libraries of 10 8 members.